Lympho-vascular invasion in oral cavity cancers – A bridge between tumour biology and clinical outcomes - Sapna Krishnamurthy; Imtiaz Ahmed; Kumar Vinchurkar; Mahesh Kalloli; Adarsh Sanikop; Raghavendra Sagar; Santosh Mathapathi; Rohan Bhise (Oral Oncology Reports)
Objective: Various histo-pathological prognostic factors have been identified in oral cavity squamous cell carcinomas (OCSCC). One such factor is the status of lympho-vascular invasion (LVI). We carried out this analysis to evaluate the association of LVI with other prognostic factors and the clinical outcomes. Methods: Data of patients with OCSCC who underwent curative intent surgery from January-2017 to December-2019 at our institute were retrospectively evaluated. The association of LVI with various tumour-node related prognostic factors and its effect on overall and disease-free survival (OS, DFS) were analyzed. Results: of the total 234 patients, 71 % (166) had Bucco-alveolar-complex primary. 62.8 % (147) had locoregionally advanced disease. 91.5 % (214) required adjuvant treatment.The LVI positivity was 77.4 %, 63.3 % in tumour size >3cm/<3 cm, 85 %, 59.7 % in depth of infiltration >1cm/<1 cm, 82.4 %, 57.6 % in T3-T4/T1-2, 91.9 %, 59.9 % in grade 3/others and 96.8 %, 13.8 % in perineural invasion present/absent, respectively (p < 0.05). In the presence of LVI, lymph node positivity was 60.6 %, N2–N3 were 41.9 % and extra-capsular extension was 26.9 % as compared to LVI negative – 5.4 %, 5.4 % and 4.1 % respectively (p < 0.05).With median follow up of 37.3 months, 2year OS and DFS were 76.6 % and 75.5 % respectively. The 2year OS and DFS for the LVI-positive group were 70.4 % and 69.3 % compared to 90.6 % and 89.3 % for LVI-negative (p = 0.00). Loco-regional and distal (any) recurrence was seen in 20.9 % (49) and 7.3 % (17), the same for LVI-positive was 25.6 % (41) and 10 % (16) compared to 10.8 % (8) and 1.4 % (1) for LVI-negative (p < 0.05). Conclusion: In oral cavity cancers, there is positive association of LVI with various tumour-node related prognostic factors and clinical outcomes.